2006
DOI: 10.1016/j.neuroimage.2006.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between a verbal working memory network and the medial temporal lobe

Abstract: The irrelevant speech effect illustrates that sounds that are irrelevant to a visually presented short-term memory task still interfere with neuronal function. In the present study we explore the functional and effective connectivity of such interference. The functional connectivity analysis suggested an interaction between the level of irrelevant speech and the correlation between in particular the left superior temporal region, associated with verbal working memory, and the left medial temporal lobe. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 76 publications
3
19
1
Order By: Relevance
“…However, no significant effect of content was found during preparation or rehearsal stages. These results are inconsistent with previous studies that have implicated distinct roles for MTL regions object and spatial working memory (Stern et al, 2001;Petersson et al, 2006;Olson et al, 2006a,b;Nichols et al, 2006;Axmacher et al, 2007Axmacher et al, , 2008. Such studies have demonstrated a role of the MTL and inferior temporal cortex in active maintenance of novel information.…”
Section: Discussioncontrasting
confidence: 96%
“…However, no significant effect of content was found during preparation or rehearsal stages. These results are inconsistent with previous studies that have implicated distinct roles for MTL regions object and spatial working memory (Stern et al, 2001;Petersson et al, 2006;Olson et al, 2006a,b;Nichols et al, 2006;Axmacher et al, 2007Axmacher et al, , 2008. Such studies have demonstrated a role of the MTL and inferior temporal cortex in active maintenance of novel information.…”
Section: Discussioncontrasting
confidence: 96%
“…On the other hand, our results may also partly reflect reciprocal attenuation between lateral prefrontal and parietal regions (e.g., Greicius et al, 2003). Future research will need to address the functional connectivity patterns to uncover interactions between the neural networks involved in different aspects of language comprehension (e.g., Petersson et al, 2006).…”
Section: Referential Ambiguity and Medial Prefrontal Regionsmentioning
confidence: 83%
“…Using seeds in the bilateral hippocampus, patients with AD demonstrated markedly reduced functional connectivity with the prefrontal cortex (Allen et al, 2007;Wang et al, 2006). Hippocampal-prefrontal connectivity has been shown to contribute to WM in several functional connectivity studies of fMRI data (Axmacher et al, 2008;Petersson et al, 2006;Rissman et al, 2008). More specifically, evidence suggests that these two regions serve complementary roles during WM processes (Hasselmo and Stern, 2006;Stern et al, 2001).…”
Section: Discussionmentioning
confidence: 99%